Perspective on pH adjustment in hydrometallurgical recycling of valuable metals from waste - Suiyi, Zhu; Jian, Wang; Yuhong, Huang; Ying, Wang; Yuxin, Zhang; Jiabao, Qin; Jiancong, Liu; Jinlu, Yao; Meichun, Ji (Frontiers in Chemistry, 2023)
pH adjustment was considered a simple step in the hydrometallurgy process, but its complicated operation was ignored in the past. In some industrial applications, the leachate pH was slowly adjusted by a diluted alkaline solution, with the defects of doubling the leachate volume and causing droplet hydrolysis/coagulation. Up to date, promising routes have been developed for rapid pH adjustment, especially in sealed high-temperature/pressure vessels. New routes emerged in some redox/decomposition reactions of nitrate/urea and organics. Such reactions did not start and/or were slow at room temperature but started spontaneously at high temperatures to generate/consume free H+. This induced pH adjustment in a rapid and homogeneous way.